The Use of Biology-Based Learning Module Android and Their Effect on Learning Outcomes on Coordination System Materials in Class XI IPA in Mas Islamiah Kotapinang - Riskiana Siregar; Hasmi Syahputra Harahap (Budapest International Research and Critics University, 2022)
This study aims to determine The Use of Android-Based Biology Learning Modules and Its Effect on Learning Outcomes in the Coordination System Material for Class XI Science at MAS Islamiyah Kota PinangThis research method uses a quantitative approach with a quasi-experimental type of research. The population in this study were students of class XI IPA MAS Islamiyah Kota Pinang. The samples used in this study were students of class XI IPA (experimental class) and class XI IPA B (control class). The sample used in this study was taken as many as 2 classes totaling 60 students. Sampling in this study was conducted using random sampling technique. Sampling in this study was carried out using a random sampling technique, In data analysis, prerequisite tests were carried out in the analysis such as the normality test for the data distribution and the homogeneity of variance test. To be able to test the homogeneity of variance, it was tested using the F test. If F count F table, the two populations have different variances (not homogeneous), If F count < F table then the two populations have homogeneous variance. The results of the research value in the control class that the higher score using the Android-Based Biology Learning Module is the result of the 57.2 experimental class using the Android-Based Biology Learning Module, which has a value of 67.4